2006
DOI: 10.1128/jcm.44.2.637-639.2006
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of a New Chromogenic Medium, MRSA Select , to CHROMagar MRSA and Mannitol-Salt Medium Supplemented with Oxacillin or Cefoxitin for Detection of Methicillin-Resistant Staphylococcus aureus

Abstract: MRSASelect agar was compared to CHROMagar, mannitol-salt agar with oxacillin, and mannitol-salt agar with cefoxitin (MSA-CFOX) for the isolation of methicillin-resistant Staphylococcus aureus (MRSA). The sensitivities and specificities were 97.3% and 99.8%, 82.9% and 99.1%, 80.2% and 79%, and 99.1% and 84.8%, respectively. MSA-CFOX and MRSASelect had a high sensitivity. MRSASelect, however, was more specific and proved to be a more reliable and rapid medium for the detection of MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
76
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 15 publications
3
76
1
1
Order By: Relevance
“…However, the present study has found that the kit has an even lower sensitivity, with the LoD being 10-fold higher than the quoted value and no better than the LoD of direct culture on CA. Although the CA used in the present study (MRSA-Select) has recently been shown to recover MRSA with a sensitivity of 97%-99% compared with other culture media [13,14], a molecular assay would be expected to have a lower LoD than culture [12]. However, our study has shown that salt enrichment culture followed by subculture onto CA and MMSA yields an improved sensitivity and a 10-fold lower LoD compared with the kit.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the present study has found that the kit has an even lower sensitivity, with the LoD being 10-fold higher than the quoted value and no better than the LoD of direct culture on CA. Although the CA used in the present study (MRSA-Select) has recently been shown to recover MRSA with a sensitivity of 97%-99% compared with other culture media [13,14], a molecular assay would be expected to have a lower LoD than culture [12]. However, our study has shown that salt enrichment culture followed by subculture onto CA and MMSA yields an improved sensitivity and a 10-fold lower LoD compared with the kit.…”
Section: Discussionmentioning
confidence: 76%
“…More recently, sensitivities of 89% with nasal specimens and 82% with groin specimens were reported when comparison was made a Direct and enrichment culture results b Amended results: see footnote to Table 3 Table 4 Sensitivity, specificity and positive (PPV) and negative (NPV) predictive values expressed as a percentage for the IDI-MRSA kit compared with culture from nose, throat and groin/perineum specimens (numbers in parentheses 95% confidence intervals, All, PPP all sites from previously positive patients, All, NPP all sites from patients with no record of being previously positive) against direct and enrichment culture on MSA containing oxacillin (OMSA) [17]. Studies comparing culture media selective for MRSA have shown that OMSA has sensitivities ranging from 60% to 84%, whereas the CA used in the present study (MRSA-Select) has a sensitivity of 97%-99% [1,13,14]. Another evaluation of the IDI-MRSA kit reported a sensitivity of 100% for the kit compared with culture on CHROMagar MRSA but, again, that medium was found to have a sensitivity of only 83% [13,18].…”
Section: Discussionmentioning
confidence: 83%
“…aureus (MRSA) is considered one of the most virulent pathogens in hospitals and intensive care units (ICU) worldwide (Pape et al, 2006). MRSA was found to be the most common pathogen identified in the United States hospitals (Stoakes et al, 2006) and accounts for 63% of nosocomial infections in Egypt (Borg et al, 2007). Moreover, new strains of MRSA associated with aggressive infections in young, otherwise healthy patients have emerged in the community (Stoakes et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MRSA was found to be the most common pathogen identified in the United States hospitals (Stoakes et al, 2006) and accounts for 63% of nosocomial infections in Egypt (Borg et al, 2007). Moreover, new strains of MRSA associated with aggressive infections in young, otherwise healthy patients have emerged in the community (Stoakes et al, 2006). Several studies have demonstrated that the MRSA infected patients tend to have longer hospital and ICU stays, higher rates of ventilator use, greater risks of death, and more adverse clinical outcomes (such as renal failure and hemodynamic instability) as compared to those patients infected with methicillin sensitive Staph.…”
Section: Introductionmentioning
confidence: 99%
“…, [9], [11,12] [7], [12,13] [9], [12] [6], [8][9][10][11][12] [6], [8,9], [11,12] [12] [7], [9][10][11], [13] [9], [11], [13] [9] [6,7], [9], [12,13] …”
mentioning
confidence: 99%